GAMBARAN TOTAL DAN DIFERENSIAL LEUKOSIT AYAM BROILER YANG DIBERI AGRIMINOVITÂ® - , WILLY MORIS NAINGGOLAN; , Dr. drh. Agustina Dwi Wijayanti, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
AgriminovitÂ® is a multivitamin contains a combination of vitamins and amino acids to meet the needs of chickenâs vitamins and amino acids, copes stress and improve production quality. The purpose of this study was to determine the effect of AgriminovitÂ® for white blood cell (WBC) count and leukocyte differentials of broiler chickens. One hundred chickens were divided into four groups, each 25 and raised since day old chick (DOC) till 35 days old. The control group was just given water ad libitum, while the treatment groups I, II, and III were given AgriminovitÂ® solution with each dose of 0.25 g/L, 0.5 g/L, and 0.75 g/L as the instructions on the package (1 g for 2 L of water for 4 days) on days 1-4, 11-15, and 21-25. Blood sampling performed at day 35 through the brachial vein of the five chicken samples that selected from each group by a simple random sampling method. Data results of WBC and leukocyte differentials were analyzed with one-way analysis of variance (ANOVA). The results showed that the administration of AgriminovitÂ® did not affect the WBC count and leukocyte differentials, so that the product is safe for consumption by chickens.